2022
DOI: 10.1002/ecy.3908
|View full text |Cite
|
Sign up to set email alerts
|

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines

Abstract: DailyNorth Atlantic Oscillation index values were downloaded from National Weather Service Climate Prediction Center (www.cpc.ncep.noaa.gov) as described in Appendix S2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…While we focus primarily on temperature, global climate change is also altering a variety of biotic and abiotic gradients [123] and endocrine flexibility likely plays a role in responding to each of these. The field stands at an exciting crossroads, and there are many opportunities to establish connections between endocrine flexibility and the approaches and techniques employed in recent studies of behavioural, phenological or morphological responses to climate change [6,10,12,100,124]. Whether similar eco-geographic patterns exist for endocrine flexibility and whether those patterns are changing predictably with climate change is an open question.…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
“…While we focus primarily on temperature, global climate change is also altering a variety of biotic and abiotic gradients [123] and endocrine flexibility likely plays a role in responding to each of these. The field stands at an exciting crossroads, and there are many opportunities to establish connections between endocrine flexibility and the approaches and techniques employed in recent studies of behavioural, phenological or morphological responses to climate change [6,10,12,100,124]. Whether similar eco-geographic patterns exist for endocrine flexibility and whether those patterns are changing predictably with climate change is an open question.…”
Section: Future Directions and Open Questionsmentioning
confidence: 99%
“…This is despite the fact that life‐history strategies and responses to food availability can vary dramatically across populations of a single species (e.g., Gamelon et al., 2021; Nilsen et al., 2009). A more thorough look at among‐population variation in traits and responses to environmental change may identify important axes of covariation in population sensitivity to environmental variation (Vriend et al., 2023). Another thing that remains to be seen is whether the differences in previous studies the authors observe in life‐history responses to environmental change is due to the use of mechanistic demographic models or are, at least in part, due to using aquatic species, which have been shown to employ different strategies compared with terrestrial animals to respond to environmental change (Capdevila et al., 2020).…”
Section: Figurementioning
confidence: 99%
“…Spatial synchrony can be important for population stability (Paradis 1997;Ruxton 1994), but highly synchronous dynamics may impose a risk of species extinction if density crashes occur simultaneously (Heino et al 1997). Research has identified spatial synchrony in survival (Olmos et al 2020), body mass (Herfindal et al 2020), breeding success (Olin et al 2020;Vriend et al 2023), phenological timing (Vriend et al 2023), and population size (Bjørnstad et al 1999a;Hansen et al 2020;Koenig 1999), particularly in birds (Mortelliti et al 2015;Paradis et al 1999Paradis et al , 2000Saether et al 2007). However, despite the interrelated dynamics between variation in population growth and age structure, there has been little research into spatial synchrony of age structure and the mechanisms that might drive this.…”
Section: Introductionmentioning
confidence: 99%